PRODUCT DEVELOPMENT FROM A DISTANCE: how does remote working affect organizational learning in new product development activities? A case study from the mobile games industry - Lohivesi, Oskari (My University, 2022)
During the year 2020 Covid-19 pandemic disrupted how knowledge work is done. By a verdict, many of the world’s office workers started to do their work from their homes to avoid the unnecessary spread of the virus. Change to the home environment rapidly changed the organizational information networks drastically from what they used to be. This thesis was an assignment from a Finnish mobile game studio Studio X to study the changes in the agile learning organization during this change and analyze the sources of the changes and the underlying reasons. According to the analysis, the most significant changes to the organization were related to information transfer and information transfer events. These detected changes were consistent with studies of Yang (2021), and through these changes, it seems that the changed environment made the process of organizational learning more difficult and time-consuming. Difficulties derived from the lack of common coworking spaces, where managers and employees could constantly communicate in informal, spontaneous, and unstructured settings. People worked together less, leading to diminished teamwork and team learning. In addition, creating a shared vision for the product was more difficult, and product development activities associated with explorative learning were perceived to be more effortful and time-consuming. These factors lead to a perceived diminishment of organizational learning capabilities. Worsened organizational learning capabilities would make it more difficult to interpret changes in the market and competitors. An organization’s ability to interpret reality is vital for reducing uncertainty in product decision-making and helping managers make the right contextual product development decisions (McNally 2013 Havermans 2015). However, in the face of constant market dynamism (Junni 2013), reduced learning capabilities could lead to an imbalance of explorative and exploitative activities, resulting in the company's risk of falling into learning traps. (Siren, Kohtamäki, Kuckertz 2012)
Keywords: product development; development (active); learning organisation; learning; remote work; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development